Kehadiran Mahasiswa IAIN Kediri dalam Transformasi Nilai (Studi Kasus di Kelurahan Ngronggo dan Rejomulyo Kota Kediri) - Huda, Syamsul; Zunairoh, Yuyun (JoIEM (Journal of Islamic Education Management), 2021)
This research aims to describe the form of presence of IAIN Kediri students in the transformation of religious, economic and cultural values ​​in Ngronggo and Rejomulyo Villages, Kediri City. Students who are considered to be the compass of transformation from the 'riotous' period of adolescence to adulthood, thinking critically-progressive-transformatively are able to impact social change, maintaining moral values ​​(guardian of values) especially in the surrounding community. Researchers used a qualitative descriptive research approach. This type of research is a case study. Namely, examining the case of the presence of IAIN Kediri students in the transformation of religious, economic and cultural values ​​in Ngronggo and Rejomulyo Villages, Kediri City objectively, critically and comprehensively. The results of this research are the transformation of values ​​provided by the presence of students in Ngronggo and Rejomulyo subdistricts, namely religion, economics and culture as follows: 1. Religion, this is proven by the large number of TPQ, Muezzin and Marbot mosques around the two villages. Economy, as evidenced by the proliferation of shops, food stalls, boarding houses, laundries, photocopiers and Islamic boarding schools. Social and Cultural, as evidenced by the activities carried out by residents, there is always involvement of students and female students. 2. The institution provides funds and activities entrusted to student organizations in order to learn about organization, community, talent, arts, etc.